2011
DOI: 10.1007/s10706-011-9419-8
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Slope Stability of Embankments Constructed with Pond Ash

Abstract: Utilization of pond ash in large earthworks for geotechnical applications like construction of highway embankments, raising of ash dykes and filling low lying areas (construction fills), solves the waste disposal problem besides conserving the natural soils. However, design and construction of such geotechnical structures particularly in earthquake prone areas, requires thorough understanding of dynamic response of these structures under different seismic loading conditions. Here in this article, dynamic stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 15 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that liquefaction leads to a significant reduction in the safety factors of tailings dams [146]. In addition, the construction method of the dam body, the particle size of the tailings, and the magnitude of the earthquake all affects the stability of the tailings dam during an earthquake [147].…”
Section: Earthquake Action Causes the Tailings Reservoir To Break Thementioning
confidence: 99%
“…Studies have shown that liquefaction leads to a significant reduction in the safety factors of tailings dams [146]. In addition, the construction method of the dam body, the particle size of the tailings, and the magnitude of the earthquake all affects the stability of the tailings dam during an earthquake [147].…”
Section: Earthquake Action Causes the Tailings Reservoir To Break Thementioning
confidence: 99%
“…In this paper, *Address correspondence to this author at the School of Civil Engineering and Architecture, Southwest Petroleum University, Chengdu 610500, P.R. China; E-mail: 120138424@qq.com on the basis of the fluid structure interaction calculation module in the software Geo-Studio and Biot theory [8,9], finite element is adopted to build the equation, in which the node displacement and the pore water pressure are unknown at the same time [10][11][12]. Once the equations are solved, seepage field and stress field are obtained simultaneously [13][14][15].…”
Section: The Fundamental Of Seepage Field and Stress Field Coupling Amentioning
confidence: 99%
“…The raised embankment is generally constructed with either of the following raising methods: upstream, downstream or centerline [1]. Of the raised embankment construction, the downstream method is the most stable construction [2,3,1].…”
Section: Introductionmentioning
confidence: 99%